Regulation of polyhydroxybutyrate synthesis in the soil bacterium Bradyrhizobium diazoefficiens - Quelas, Juan Ignacio (2016)
Polyhydroxybutyrate (PHB) is a carbon and energy reserve polymer in various prokaryotic species. We determined that, when grown with mannitol as the sole carbon source, Bradyrhizobium diazoefficiens produces a homopolymer composed only of 3-hydroxybutyrate units (PHB). Conditions of oxygen limitation (such as microoxia, oxic stationary phase, and bacteroids inside legume nodules) were permissive for the synthesis of PHB, which was observed as cytoplasmic granules. To study the regulation of PHB synthesis, we generated mutations in the regulator gene phaR and the phasin genes phaP1 and phaP4. Under permissive conditions, mutation of phaR impaired PHB accumulation, and a phaP1 phaP4 double mutant produced more PHB than the wild type, which was accumulated in a single, large cytoplasmic granule. Moreover, PhaR negatively regulated the expression of phaP1 and phaP4 as well as the expression of phaA1 and phaA2 (encoding a 3-ketoacyl coenzyme A [CoA] thiolases), phaC1 and phaC2 (encoding PHB synthases), and fixK2 (encoding a cyclic AMP receptor protein [CRP]/fumarate and nitrate reductase regulator [FNR]-type transcription factor of genes for microoxic lifestyle). In addition to the depressed PHB cycling, phaR mutants accumulated more extracellular polysaccharides and promoted higher plant shoot dry weight and competitiveness for nodulation than the wild type, in contrast to the phaC1 mutant strain, which is defective in PHB synthesis. These results suggest that phaR not only regulates PHB granule formation by controlling the expression of phasins and biosynthetic enzymes but also acts as a global regulator of excess carbon allocation and symbiosis by controlling fixK2.